these are the answers



in Calculus Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

f(x) = 3x - 1. g(x) = x + 4. h(x) = x2. Then (h o f)(x) =

We can ignore g(x) above, giving us,

f(x) = 3x – 1, h(x) = x^2. Then (h o f)(x) =

Since (h o f)(x) means h(f(x)), where h(f(x)) is the function h() with f(x) as its argument, then

since h(x) = x^2, then h(f) = f^2, i.e.

h(f(x)) = (f(x))^2 = (3x – 1)^2

h(f(x)) = 9x^2 – 6x + 1.

Comparing the last result with the possible answers given, the correct choice is,

Option F) 9x^2 – 6x + 1

by Level 11 User (80.8k points)

Related questions

1 answer
1 answer
1 answer
asked Dec 6, 2012 in Algebra 1 Answers by anonymous | 141 views
1 answer
1 answer
asked Oct 17, 2012 in Calculus Answers by anonymous | 122 views
Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
84,070 questions
89,003 answers
6,764 users